Individual Keratinocyte Necroses in the Epidermis Are Apoptotic Keratinocytes in the Skin - Mitsuhiro Tachibana; Hideki Hamayasu; Kazuki Tomita; Yuta Kage (Diagnostics, 2023)
The patient was a 44-year-old woman with Stevens–Johnson syndrome due to receiving Baktar® (sulfamethoxazole trimethoprim) medication at our outpatient dermatology clinic. The epidermis, dermis, and subcutaneous adipose tissue samples showed numerous necrotic keratinocytes in the epidermis. Apoptotic nuclei were visualized as diaminobenzidine brown deposits with immunoperoxidase staining for cleaved caspase-3. The cleaved caspase-3-positive findings were consistent with eosinophilic material that appeared to be necrotic cells within the epidermis. Therefore, these eosinophilic materials may be apoptotic bodies. Generally speaking, eosinophilic cells are considered necrotic keratinocytes, especially in Japan. To the best of our knowledge, no studies have used apoptotic immunohistochemical markers to examine whether these structures are apoptotic in a human specimen.